2017
DOI: 10.1038/srep41984
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling of reactive persulfides and polysulfides in the aqueous and vitreous humors

Abstract: We investigate the metabolomic profile of reactive persulfides and polysulfides in the aqueous and vitreous humors. Eighteen eyes of 18 consecutive patients with diabetes mellitus (DM) and diabetic retinopathy underwent microincision vitrectomy combined with cataract surgery. Samples of the aqueous and vitreous humors were collected and underwent mass spectrometry-based metabolomic profiling of reactive persulfides and polysulfides (polysulfidomics). The effect of reactive polysulfide species on the viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…However, the majority of m/z signals remain unidentified, particularly in the black bream potentially due to the lack of ocular humour analysis of teleost eyes, and their identification would allow additional interpretation of their possible biological significance to be made. In the rabbit eyeball analysis, the trends of our provisionally identified ocular humour metabolite distributions were consistent with previous studies, where cystine (the more stable, oxidised form of cysteine), uric acid, and citric acid have been detected in AH at higher abundance than VH, and taurine, as an important molecule that supports retinal photoreceptor cell function, has been detected at higher levels in the VH than AH . Complementary orthogonal LC‐MS metabolomics studies would aid greatly in identifying endogenous metabolites but are beyond the scope of this method.…”
Section: Discussionsupporting
confidence: 86%
“…However, the majority of m/z signals remain unidentified, particularly in the black bream potentially due to the lack of ocular humour analysis of teleost eyes, and their identification would allow additional interpretation of their possible biological significance to be made. In the rabbit eyeball analysis, the trends of our provisionally identified ocular humour metabolite distributions were consistent with previous studies, where cystine (the more stable, oxidised form of cysteine), uric acid, and citric acid have been detected in AH at higher abundance than VH, and taurine, as an important molecule that supports retinal photoreceptor cell function, has been detected at higher levels in the VH than AH . Complementary orthogonal LC‐MS metabolomics studies would aid greatly in identifying endogenous metabolites but are beyond the scope of this method.…”
Section: Discussionsupporting
confidence: 86%
“…Nakazawa and colleagues reported the endogenous occurrence of persulfide species in the aqueous and vitreous humour [ 7 ]. They measured persulfides and polysulfides by means of LC-MS/MS with HPE-IAM, and found that patients with diabetes mellitus (DM) had elevated levels of CysSSH, cystine, and GSSSG in the aqueous humour compared with healthy subjects.…”
Section: Endogenous Occurrence Of Cysssh and Related Moleculesmentioning
confidence: 99%
“…Cysteine persulfide (CysSSH) and cysteine polysulfides (CysSS n H, n > 1) are cysteine derivatives that have sulfane sulfur atoms that are bound to cysteine thiol [ 1 , 2 , 3 , 4 ]. Various forms of persulfides/polysulfides exist in both prokaryotes and eukaryotes as low-molecular-weight compounds, such as CysSSH, homocysteine persulfide, glutathione persulfide (GSSH), glutathione trisulfide (GSSSH), oxidized glutathione trisulfide (GSSSG), bacillithiol persulfide, and coenzyme A persulfide, and as CysSSHs in proteins ( Figure 1 ) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Persulfide species have been suggested to be involved in various biological processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations